GAMBARAN BUDAYA GENERASI MILENIAL DI KOTA SURABAYA DITINJAU DARI ENAM DIMENSI BUDAYA HOFSTEDE - Ikhwan Fadlu Fantazilu (Universitas Pendidikan Ganesha, 2022)
This study aims to determine how the cultural picture of the millennial generation in the city of Surabaya is viewed from the six dimensions of Hofstede's culture. This research is a quantitative research that uses the